Woman's work in literature - Olson, Bertha A. (My University, 1897)
Introduction: The increase in the number of female writers in this country has been very rapid. They restrict themselves with a very few exceptions to poetry and fiction. Woman’s success in writing novels, stories and verses would seem to settle all doubts as to her ability to compete with man in the field of literature. She puts much of her personal individuality into her book, being more prone to express emotions than ideas, and she also risks more than a man. To most women, fame, except so far as it bears the character of sympathy, is more an annoyance than a pleasure. Fame is hardly her object in taking up the pen; and she is surprised and wounded by criticism on mere literary defects, having expected from the world in general, the indulgent sympathy which she has found among partial friends. In many female writers is recognized an earnest and holy spirit and true aim, inconsistent with a petty love of display. The less absorbing nature of female occupations is favorable to wanderings through the gardens of imagination and fancy.
Citation: Olson, Bertha A. Woman's work in literature. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Women; Authors; Literature; Theses; Manuscripts (documents)